Angka kuman di ruang rawat inap RSUD Dr. M. Haulussy Ambon - Tina Amnah Ningsih; Susi Iravati; Titik Nuryastuti (Berita Kedokteran Masyarakat (BKM), 2016)
The number of bacteria in the inpatient rooms of RSUD Dr. M. Haulussy Ambon HospitalPurpose The purpose of this study was to determine the total number of germs and identify factors related to the number of germs in the inpatient wards of RSUD dr. M. Haulussy Ambon Hospital.MethodsThis observational study used a cross-sectional design. The space objects used for samples were internal wards, surgical wards, and neurological wards of RSUD. Dr. M. Haulussy Ambon.ResultsThe temperature had a significant relationship with the number of morning air germs. Lighting had a significant relationship with the numbers of germs in the afternoon air and on the afternoon floor.ConclusionsThis study showed that the number of germs in the air, on the walls, and floors in the hospital wards of Dr. M. Haulussy Ambon did not fulfil the requirements according to Kepmenkes no. 1204/Menkes/SK/X/2004. It is necessary to improve the quality of temperature and lighting in order to reduce the number of germs in hospital wards.